Boron nitride modified heat-conducting glass fiber reinforced composite material and preparation method thereof
Through solvent-induced self-assembly technology, modified boron nitride and aramid fiber sol are used to soak glass fibers multiple times to form a thermal conductivity network, which solves the problems of poor thermal and mechanical properties of existing composite materials, and significantly improves thermal conductivity and Mechanical properties while maintaining insulation.
Patent Information
- Application Number
- CN202411524826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
After filling with high thermal insulation materials, existing thermally conductive insulating materials have problems such as poor dispersion performance, poor mechanical properties and poor thermal conductivity, which leads to the comprehensive performance of composite materials being unable to meet market application needs.
The micro-phase separation semi-continuous thermal network is constructed through solvent-induced self-assembly, and the continuous glass fiber is soaked multiple times by using modified boron nitride and aramid fiber sol to fix the boron nitride on the fiber surface to form a continuous thermal path and thermal network. Improve the thermal conductivity and mechanical properties of composite materials.
The thermal conductivity and mechanical properties of the composite material are significantly improved, the thermal conductivity and tensile strength are improved, and the insulation performance is maintained, solving the problems of poor filler deposition and bonding in the prior art.
Smart Images

Figure CN119286007A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a boron nitride modified thermally conductive glass fiber reinforced composite material and a preparation method thereof. Background Art
[0002] In recent years, the green and low-carbon transformation of my country's energy and power industry has been deeply promoted. The installed capacity of hydropower, wind power, photovoltaic, biomass power generation and the installed capacity of nuclear power under construction have remained the world's first. The scale of power equipment has gradually expanded, and the power transmission power has gradually increased. Due to the Joule effect, power equipment will generate a lot of heat in the process of transmitting electricity. If the heat cannot be dissipated in time and effectively, it will cause the local temperature of the equipment to rise, aggravating the power transmission loss. Therefore, in order to improve the efficiency of power transmission, high thermal conductivity insulation materials are usually filled into the matrix material to enhance the thermal conductivity and heat dissipation performance of the material. However, the existing thermal conductive insulation materials still have problems such as poor dispersion performance caused by high filling, poor mechanical properties of products, and poor thermal conductivity. For example, the Chinese invention patent with application number CN 118325288A discloses a preparation technology for high thermal conductivity continuous glass fiber winding reinforced epoxy resin composite materials, and the specific method is: after the continuous glass fiber is passed through the glue mixed with inorganic thermal conductive fillers, wet winding is performed to obtain a high thermal conductivity composite material. However, this method has problems such as difficulty in dispersing inorganic thermal conductive fillers, which are easily deposited at the bottom of the material tank, poor bonding with glass fibers, and easy to fall off from the surface of glass fibers. Therefore, the actual application effect of this method is poor, and there is no possibility of expanding production. Summary of the invention
[0003] The main purpose of this application is to provide a boron nitride modified thermally conductive glass fiber reinforced composite material and a preparation method thereof, aiming to solve the technical problem that the comprehensive properties of existing composite materials such as thermal conductivity, mechanics, and insulation cannot meet the market application requirements.
[0004] To this end, the first technical solution of the present application provides a boron nitride modified thermally conductive glass fiber reinforced composite material and a preparation method thereof, comprising the following steps:
[0005] dissolving the aramid fiber to obtain an aramid fiber solution;
[0006] Adding KH550 to the boron nitride dispersion, separating the substrate and dispersing it after ultrasonic modification to obtain a modified boron nitride dispersion;
[0007] The modified boron nitride dispersion is mixed with the aramid fiber solution to obtain an aramid fiber / boron nitride sol;
[0008] The continuous glass fiber is immersed in isopropyl alcohol and aramid / boron nitride sol in sequence, which is regarded as a cycle, and the cycle is repeated until the phase conversion process is completed to obtain a modified thermally conductive glass fiber;
[0009] The modified thermally conductive glass fiber is dried, chopped, mixed with a resin matrix mixture, and cured by high-temperature molding to obtain a boron nitride modified thermally conductive glass fiber reinforced composite material;
[0010] Among them, in the boron nitride dispersion and KH550, the mass ratio of boron nitride to KH550 is 20-200:1; in the modified boron nitride dispersion and aramid fiber solution, the mass ratio of boron nitride to aramid fiber is 1-20:1.
[0011] Furthermore, the particle size of the boron nitride is at least two of 1 μm, 5 μm, 10 μm, 20 μm, and 40 μm.
[0012] Furthermore, the solvent for dissolving the aramid fiber is a solution of potassium hydroxide and dimethyl sulfoxide.
[0013] Furthermore, the dispersant of the boron nitride dispersion is a mixed solution of ethanol and deionized water, and the mass ratio of ethanol to deionized water is 1:1-10.
[0014] Furthermore, the ultrasonic modification power is 500w and the time is 2h.
[0015] Furthermore, the dispersant used for dispersion after separation of the substrate is dimethyl sulfoxide.
[0016] Furthermore, after the modified boron nitride dispersion is mixed with the aramid fiber solution, zinc ricinoleate is added to the mixture to obtain an aramid fiber / boron nitride sol.
[0017] Furthermore, the initial concentration of the aramid / boron nitride sol is 1 to 120 mg / mL.
[0018] Furthermore, the curing temperature is 140-160° C., and the curing time is 8-12 minutes.
[0019] And, a boron nitride modified thermally conductive glass fiber reinforced composite material prepared according to the above preparation method.
[0020] Beneficial effects: In order to improve the thermal conductivity of existing composite materials, high thermal conductivity fillers are usually filled into the matrix material. Common fillers include graphene, carbon nanotubes, boron nitride, aluminum oxide and magnesium oxide. However, after adding a large amount of the above fillers, the product has no insulation or poor mechanical properties. Compared with the prior art, the present application constructs a microphase separation semi-continuous thermal conductive network through solvent-induced self-assembly to obtain a high-strength and high-thermal conductivity glass fiber reinforced composite material: the modified thermal conductive glass fiber is prepared by soaking continuous glass fiber in isopropanol, and then immersing it in aramid / boron nitride sol, and repeating the phase conversion process several times. Aramid is transferred from a good solvent to a poor solvent, and aramid crystallizes and precipitates on the surface of the glass fiber cloth and fixes boron nitride on the surface to complete the thermal conductivity modification of the glass fiber. It is then compounded with a mixture of unsaturated polyester resin and other additives to complete the preparation of the composite material. The modified boron nitride is attached to continuous glass fibers, with the glass fibers as the skeleton, and the fillers are overlapped with each other to form a continuous heat conduction path and heat conduction network inside the composite material, thereby improving the thermal conductivity and mechanical properties of the obtained composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Attached Figure 1 This is a SEM scan of the aramid / boron nitride sol modified glass fiber of Example 1;
[0022] Attached Figure 2 This is the SEM scanning image of the glass fiber modified by the modified boron nitride dispersion in comparative example 2. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0025] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0026] The embodiment of the present application provides a boron nitride modified thermally conductive glass fiber reinforced composite material and a preparation method thereof, comprising the following steps:
[0027] dissolving the aramid fiber to obtain an aramid fiber solution;
[0028] Adding KH550 to the boron nitride dispersion, separating the substrate and dispersing it after ultrasonic modification to obtain a modified boron nitride dispersion;
[0029] The modified boron nitride dispersion is mixed with the aramid fiber solution to obtain an aramid fiber / boron nitride sol;
[0030] The continuous glass fiber is immersed in isopropyl alcohol and aramid / boron nitride sol in sequence, which is regarded as a cycle, and the cycle is repeated until the phase conversion process is completed to obtain a modified thermally conductive glass fiber;
[0031] The modified thermally conductive glass fiber is dried, chopped, and mixed with a resin matrix mixture, and then cured by high-temperature film pressing to obtain a boron nitride modified thermally conductive glass fiber reinforced composite material;
[0032] Among them, in the boron nitride dispersion and KH550, the mass ratio of boron nitride to KH550 is 20-200:1; in the modified boron nitride dispersion and aramid fiber solution, the mass ratio of boron nitride to aramid fiber is 1-20:1.
[0033] In this embodiment, the particle size of the boron nitride is at least two of 1 μm, 5 μm, 10 μm, 20 μm, and 40 μm. A high thermal conductive filler is obtained by compounding boron nitrides with different particle sizes.
[0034] In this embodiment, the solvent for dissolving the aramid fiber is a solution of potassium hydroxide and dimethyl sulfoxide.
[0035] In this embodiment, the boron nitride dispersion is obtained by dispersing boron nitride using a mixed solution of ethanol and deionized water as a dispersant. The purpose of the dispersant is to promote the full hydrolysis of KH550 after mixing with KH550, thereby effectively modifying boron nitride; wherein the mass ratio of ethanol to deionized water is 1:1 to 10. After that, ultrasonic modification treatment is performed. In order to improve the adequacy of the modification, the ultrasonic treatment can be placed in a cell crusher while being ultrasonically treated in a water bath. After ultrasonic treatment, the modified boron nitride substrate is separated; in order to improve the separation efficiency, it is preferably used in a centrifugal washing method, and the collected substrate is ultrasonically dispersed into dimethyl sulfoxide. The purpose of using dimethyl sulfoxide as a dispersant here is to eliminate the interference of poor solvents such as water and alcohol on the aramid fiber added subsequently.
[0036] In this embodiment, the purpose of modifying boron nitride is to improve the uniformity of the overall performance of the composite material. The existing unmodified boron nitride with a larger particle size has poor dispersibility and is more prone to precipitation, which can easily cause uneven impregnation of continuous glass fibers during the impregnation process. During the pultrusion process, large-particle fillers with poor dispersibility can easily cause mold blockage; during the pressing process, especially for products with thicker thickness, filler sedimentation can easily cause a gradient in the thermal conductivity of the composite material along the thickness direction, thereby affecting the uniformity of the overall performance of the composite material. It should be noted that in the above embodiment, the power of the two ultrasonic treatments was 500w and the time was 2h.
[0037] In this embodiment, after the modified boron nitride dispersion and the aramid fiber solution are mixed, a uniform aramid fiber / boron nitride sol can be obtained by stirring. In which, based on boron nitride and aramid fiber, the mass ratio of boron nitride to aramid fiber in the modified boron nitride dispersion and the neutral aramid fiber solution is 1 to 20:1.
[0038] In a further embodiment, in order to improve the dispersibility and antioxidant properties of the modified boron nitride dispersion in the aramid / boron nitride sol, zinc ricinoleate may be added to the sol; and in order to improve the uniformity of stirring, mechanical stirring is preferably used.
[0039] In this embodiment, the phase conversion process requires that the glass fiber is first immersed in isopropyl alcohol and then immersed in aramid / boron nitride sol, and the cycle is repeated until the phase conversion process is completed.
[0040] It should be noted that this process is a process of constructing a microphase separation semi-continuous thermal conductive network by solvent-induced self-assembly. In this process, aramid is transferred from a good solvent to a poor solvent, aramid crystallizes on the surface of the glass fiber and fixes the modified boron nitride on the surface of the continuous glass fiber, thereby completing the thermal conductivity modification of the glass fiber and obtaining a modified thermal conductive glass fiber (such as Figure 1 Shown: According to Figure 1It can be seen that the modified boron nitride is completely fixed on the surface of the glass fiber).
[0041] In subsequent implementations, the modified thermally conductive glass fiber is used as a skeleton, chopped short after drying, and then mixed with a resin matrix mixture so that the fillers in the mixture overlap with each other to form a continuous thermal conductive path and thermal conductive network inside, thereby improving the thermal conductivity and mechanical properties of the obtained glass fiber composite material.
[0042] It can be understood that the resin matrix mixture is a mixture that can be understood by those skilled in the art. This application does not make specific limitations, but only provides some preferred embodiments; for example, preferably 50-120 parts of unsaturated polyester resin, 2-5 parts of curing agent, 10-30 parts of calcium carbonate, 20-80 parts of modified glass fiber, 1-10 parts of release agent; wherein the unsaturated polyester resin includes at least one of bisphenol A type unsaturated polyester resin, isophthalic unsaturated polyester resin, fumarate and maleate; the curing agent includes at least one of tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate and 1,1-di-tert-butyl peroxycyclohexane; the release agent includes at least one of zinc stearate, magnesium stearate and calcium stearate. In a preferred embodiment, the mass ratio of the modified thermally conductive glass fiber to the resin matrix mixture is 10-50:100.
[0043] In this embodiment, the curing temperature is preferably 140-160° C., and the curing time is 8-12 minutes.
[0044] The technical effects of this application will be verified through specific examples below.
[0045] Example 1 Preparation of boron nitride modified thermally conductive glass fiber reinforced composite material
[0046] 1) Soak 1 part of aramid fiber by mass in a potassium hydroxide / dimethyl sulfoxide solution and stir continuously until the aramid fiber is completely dissolved to obtain a uniform, viscous, dark red aramid fiber solution.
[0047] 2) 1 part of boron nitride with a particle size of 5 μm and 1 part of boron nitride with a particle size of 20 μm were dispersed in a mixed solution of 9 parts of ethanol and 1 part of deionized water, 0.1 parts of KH550 were added, and ultrasonic treatment was performed in a water bath with a cell crusher at a power of 500 W for 2 hours. Then, the substrate was centrifuged and washed 5 times, and the substrate was collected and ultrasonically dispersed in dimethyl sulfoxide to obtain a modified boron nitride dispersion.
[0048] 3) The modified boron nitride dispersion of 2) is mixed with the aramid fiber solution of 1), 0.02 parts of zinc ricinoleate is added, and the mixture is dispersed under mechanical stirring to form a uniform aramid fiber / boron nitride sol with a concentration of 8 mg / mL.
[0049] 4) After the continuous glass fiber is immersed in isopropyl alcohol, it is immersed in 3) aramid / boron nitride sol, and the phase conversion process is completed repeatedly once to obtain a modified thermally conductive glass fiber.
[0050] 5) The glass fibers in 4) are dried and chopped, and then mixed with a resin matrix mixture, which includes 50 parts of unsaturated polyester resin, 3 parts of curing agent, 10 parts of calcium carbonate, 7 parts of release agent, and 25 parts of modified glass fibers by mass. The mixture is cured at 150° C. for 10 minutes to obtain a modified thermally conductive glass fiber reinforced composite material with thermal conductivity and electrical insulation.
[0051] Embodiment 2:
[0052] Weigh 50 parts of unsaturated polyester resin, 3 parts of curing agent, 10 parts of calcium carbonate, 7 parts of release agent, and 30 parts of modified glass fiber by mass.
[0053] The preparation process is the same as that of Example 1.
[0054] Embodiment 3:
[0055] Weigh 50 parts of unsaturated polyester resin, 3 parts of curing agent, 10 parts of calcium carbonate, 7 parts of release agent, and 35 parts of modified glass fiber by mass.
[0056] The preparation process is the same as that of Example 1.
[0057] Comparative Example 1:
[0058] Weigh 50 parts of unsaturated polyester resin, 3 parts of curing agent, 10 parts of calcium carbonate, 7 parts of release agent, and 25 parts of glass fiber by mass.
[0059] The preparation process is the same as that of Example 1.
[0060] Comparative Example 2
[0061] The same as Example 1, except that the modified boron nitride dispersion is not mixed with the aramid solution to form a modified boron nitride / aramid sol, and the continuous glass fiber cloth is directly soaked in isopropanol and then soaked in the modified boron nitride dispersion to obtain the modified thermally conductive glass fiber.
[0062] Experimental Example 1 Microscopic Analysis of Modified Thermally Conductive Glass Fiber
[0063] The modified thermally conductive glass fibers obtained in Example 1 and Comparative Example 2 were scanned to obtain SEM scans, as shown in FIG. Figure 1 (SEM scanning image of aramid / boron nitride sol modified glass fiber of Example 1) and Figure 2(Comparative Example 2: SEM scanning image of modified boron nitride dispersion modified glass fiber) As shown: Aramid is precipitated on the surface of glass fiber and the modified boron nitride is fixed on the surface of continuous glass fiber to form a continuous heat conduction path, thereby obtaining modified heat conductive glass fiber, and finally obtaining a composite material with higher thermal conductivity ( Figure 1 ). When the modified boron nitride dispersion does not form a sol with the aramid solution but directly improves the glass fiber, the boron nitride and the glass fiber are poorly bonded, and only a trace amount of boron nitride is attached to the glass fiber, which cannot form a continuous heat conduction path, resulting in poor thermal conductivity modification of the glass fiber.
[0064] Test Example 2 Performance Test of Modified Thermally Conductive Glass Fiber Reinforced Composite Material
[0065] The products obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-2 were tested for mechanical properties, volume resistivity and thermal conductivity:
[0066] Among them, the tensile strength is tested in accordance with "GB / T 1040-2018 Determination of Tensile Properties of Plastics"; the volume resistivity is obtained by the ZC36 high insulation resistance measuring instrument; the thermal conductivity coefficient is tested by using the German NETZSCH LFA467 instrument to measure the thermal diffusion coefficient of the material, and then the DSC instrument is used to measure the specific heat capacity of the material, and then the material density is obtained according to the volume and weight of the material, and finally the thermal conductivity of the material is obtained according to the formula: thermal conductivity = thermal diffusion coefficient * specific heat capacity * density.
[0067] The test results are shown in Table 1 below:
[0068] Table 1
[0069]
[0070] It can be seen that compared with comparative examples 1 and 2, the composite materials obtained in Examples 1-3 of the present application have thermal conductivity improved by 5-7 times while ensuring tensile strength and insulation performance, indicating that the thermal conductivity of the modified glass fiber after being immersed in the modified boron nitride / aramid sol formed by the modified boron nitride and aramid solution is significantly improved.
[0071] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A boron nitride modified thermally conductive glass fiber reinforced composite material and a preparation method thereof, characterized in that: The following steps are involved: dissolving the aramid fiber to obtain an aramid fiber solution; Adding KH550 to the boron nitride dispersion, separating the substrate and dispersing it after ultrasonic modification to obtain a modified boron nitride dispersion; The modified boron nitride dispersion is mixed with the aramid fiber solution to obtain an aramid fiber / boron nitride sol; The continuous glass fiber is immersed in isopropyl alcohol and aramid / boron nitride sol in sequence, which is regarded as a cycle, and the cycle is repeated until the phase conversion process is completed to obtain a modified thermally conductive glass fiber; The modified thermally conductive glass fiber is dried, chopped, mixed with a resin matrix mixture, and cured by high-temperature molding to obtain a boron nitride modified thermally conductive glass fiber reinforced composite material; Among them, in the boron nitride dispersion and KH550, the mass ratio of boron nitride to KH550 is 20-200:1; in the modified boron nitride dispersion and aramid fiber solution, the mass ratio of boron nitride to aramid fiber is 1-20:
1.
2. The preparation method according to claim 1, characterized in that: The boron nitride particle size is at least two of 1 μm, 5 μm, 10 μm, 20 μm, and 40 μm.
3. The preparation method according to claim 1, characterized in that: The solvent for dissolving the aramid fiber is potassium hydroxide and dimethyl sulfoxide solution.
4. The preparation method according to claim 1, characterized in that: The dispersant of the boron nitride dispersion is a mixed solution of ethanol and deionized water, and the mass ratio of ethanol to deionized water is 1:1-10.
5. The preparation method according to claim 1, characterized in that: The ultrasonic modification power is 500w and the time is 2h.
6. The preparation method according to claim 1, characterized in that: The dispersant dispersed after the substrate is separated is dimethyl sulfoxide.
7. The preparation method according to claim 1, characterized in that: After the modified boron nitride dispersion is mixed with the aramid fiber solution, zinc ricinoleate is added and mixed to obtain the aramid fiber / boron nitride sol.
8. The preparation method according to claim 1, characterized in that: The initial concentration of the aramid / boron nitride sol is 1-120 mg / mL.
9. The preparation method according to claim 1, characterized in that: The curing temperature is 140-160° C., and the curing time is 8-12 minutes.
10. A boron nitride modified thermally conductive glass fiber reinforced composite material prepared according to any one of the preparation methods of claims 1-9.
Citation Information
Patent Citations
High-thermal-conductivity continuous glass fiber winding reinforced epoxy resin composite material and preparation method thereof
CN118325288A
Cited By
Glass fiber reinforced thermally conductive composite material plated with hexagonal boron nitride on the surface and preparation method thereof
CN122706133A